The Obligation to Morally Enhance Psychopaths Using Biotechnologies: A Kantian Perspective - Mdluli, Mandisa (Ethical perspectives, 2025)
This manuscript draws on the under-explored Kantian duty of moral perfection to contend that psychopaths have a moral imperative to undergo biotechnological moral enhancement via DBS (Deep Brain Stimulation). In addition, non-psychopaths are obliged to help psychopaths acquire such measures that will align them with this duty. We justify that this is necessary to free them from any inclinations that may hinder their ability to pursue their ends further. Although this manuscript has only drawn on this duty to interrogate key questions around biotechnological enhancement, we believe this duty has more value than articulated in this current manuscript. Hence, we recommend more evaluative studies that draw on this duty to interrogate other ethical questions.